Associations of neuropsychiatric symptoms with cognitive impairment: The utility of the mild behavioral impairment checklist and the neuropsychiatric interview questionnaire in a cognitive neurology clinic population. (31st December 2021) - Hu, Sophie; Patten, Scott B; Charlton, Anna; Fischer, Karyn; Fick, Gordon; Smith, Eric E.; Ismail, Zahinoor
Abstract: Background: Mild Behavioral Impairment is characterized by later life emergent and persistent neuropsychiatric symptoms (NPS). MBI domains include impaired drive/motivation, affective dysregulation, impulse dyscontrol, social inappropriateness, and psychosis. We aimed to compare the relationship between NPS and cognition in patients with subjective cognitive decline (SCD), mild cognitive impairment (MCI) and dementia, using the Mild Behavioral Impairment‐Checklist (MBI‐C) and Neuropsychiatric Inventory Questionnaire (NPI‐Q). MBI domains were derived from the NPI‐Q using a published algorithm. Method: Data was examined from 1238 patients in the PROMPT Cognitive Neurology Clinic registry at the University of Calgary. NPS were characterized at baseline using the MBI‐C (n=474) and NPI‐Q (n=1040). Forward stepwise linear regression models were conducted to compare MBI‐C and NPI‐Q total and domain scores with cognition as assessed using the Montreal Cognitive Assessment (MoCA). Age, diagnosis, sex and education were included as covariates. Result: Overall, 90% of patients had an MBI‐C total score>0 and 55.91% of patients scored above cutoff (>7). MBI prevalence (based on cutoff) was 37% in patients with SCD, 54% in MCI, and 62% of dementia patients scored above the cutoff. By domain, over half had impaired drive/motivation (59.57%), affective dysregulation (68.66%) or impulse dyscontrol (64.11%), while relatively fewer had social inappropriateness (33.97%) or psychotic symptoms (22.25%). For the NPI‐Q, 67.98% of patients had a total score>0 including 60.36% of SCD, 60.00% of MCI and 74.95% of dementia. By domain, over half had affective dysregulation (61%) or impulse dyscontrol (58.50%) while less than half had impaired drive/motivation (44.31%), social inappropriateness (23.19%) or psychosis (10.18%). With increasing diagnostic severity, age, MBI‐C and NPI‐Q scores increased, while MoCA scores decreased. Greater MBI‐C and NPI‐Q total and domain scores were significantly associated with lower MoCA score. Of all domains, psychosis had the strongest association with impaired cognition using both measures. Age, sex and diagnosis were modifiers for the MBI‐C. Conclusion: NPS are associated with poorer cognition regardless of diagnostic status. MBI domain scores are more strongly associated with impaired cognition than total scores. These findings suggest that the MBI‐C has utility in capturing NPS in this specialty clinic population, as a complement to the NPI‐Q.